2008
DOI: 10.1080/17518420701783622
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient evaluation of vision and ocular motricity in 123 children with cerebral palsy

Abstract: Visual and oculomotor tests are of significant importance in children with CP and provide relevant information for creating a rehabilitation programme aimed at the individual as a whole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…The prevalence found in our study was higher than that in the previous studies. [5][6][7] One of the reasons could be that the criteria for ametropia in previous studies were set at a higher value; however, our criteria have been used in other studies. 23 The other reason for the difference could be the strict diagnostic criteria of cerebral palsy and MRI confirmation used for enrollment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence found in our study was higher than that in the previous studies. [5][6][7] One of the reasons could be that the criteria for ametropia in previous studies were set at a higher value; however, our criteria have been used in other studies. 23 The other reason for the difference could be the strict diagnostic criteria of cerebral palsy and MRI confirmation used for enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, the subjects were older than age 4 years in most of the studies. 3,5,6,10,11 Thus, we cannot determine the association between ophthalmic and motor system development. A few reports suggested that fixation of refractive error occurred between ages 2.5 and 3 years.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Other tests include the Titmus housefly test, the Lang stereo test, the Hess screen test, red-filter test, Maddox rod evaluation, and Lancaster red-green test. 12,30 In young children, who may be less cooperative with an examiner, binocular gaze conjugacy may only be assessable with simpler algorithms, such as following an object moving in a set trajectory. 9 When such tests are performed in conjunction with the remainder of the neuro-ophthalmic and physical evaluation, one can localize neurological lesions and quantitate ocular motility deficits, particularly those associated with TBI, 18 with great accuracy.…”
Section: Discussionmentioning
confidence: 99%